Sleep quality monitoring in individual sports athletes: parameters and definitions by systematic review - Mário Antônio de Moura Simim; Helton de Sá Souza; Carlos Alberto Cardoso Filho; Rodrigo Luiz da Silva Gianoni; Roberto Rodrigues Bezerra; Helvio de Oliveira Affonso; Alberto Carlos Amadio; Vânia D’Almeida; Júlio Cerca Serrão; João Gustavo Claudino (Sleep Science, 2020)
In the present review, we identify which instruments and parameters are used for sleep quality monitoring in individual sport athletes and which definitions were used for sleep quality parameters in this literature field. Systematic searches for articles reporting the qualitative markers related to sleep in team sport athletes were conducted in PubMed, Scopus and Web of Science online databases. The systematic review followed the Preferred Reporting Items for Systematic Reviews. The initial search returned 3316 articles. After the removal of duplicate articles, eligibility assessment, 75 studies were included in this systematic review. Our main findings were that the most widely used measurement instruments were Actigraphy (25%), Rating Likert Scales (16%) and Sleep Diary (13%). On sleep quality parameters (Sleep duration = 14%; Wake after sleep onset = 14%; Sleep Quality = 12%; Sleep Effciency = 11% and Sleep Latency = 9%), the main point is that there are different definitions for the same parameters in many cases reported in the literature. We conclude that the most widely used instruments for monitoring sleep quality were Actigraphy, Likert scales and Sleep diary. Moreover, the definitions of sleep parameters are inconsistent in the literature, hindering the understanding of the sleep-sport performance relationship.